Keefektifan Kalimat Bahasa Pengantar dalam Praktik Debat Siswa Kelas X IPA Madrasah Aliyah Negeri Tanjungpinang T.A. 2017/2018 - Renaning Widyawati (TANJAK, 2021)
This study abaout discusses language as a communication tool to understand an argument in learning the practice of debate. The method used in the practice of the debate uses a scientific learning approach in accordance with the 2013 curriculum used in education units. After students observe the motion (theme) of the debate, students then arrange arguments according to the division of affirmation (support) or contra (reject) groups by using three aspects of the effectiveness of the sentences that have been determined. The three aspects in question are (1) clarity of sentence function elements, (2) freedom from structural contamination, (3) freedom from regional and foreign language interference. The results of the analysis with three grammatical aspects are presented. The results of the analysis showed an increase in the percentage after the explanation of the language so that the level of students understanding of the debate motions described through arguments could be understood better and the debate to be interestingly. On the basic of this research, it can be said that spoken language in the language of instruction in teaching and learning activities needs attention, so that the function of language as a communication tool can be carried out properly.